Bolesław Sulik — łącznik z Londynu - Tarka, Krzysztof (Archiwum Emigracji, 2012)
Bolesław Sulik (1929–2012), an emigration publicist, script writer and filmmaker, from the second half of the 60’s of the 20th century visited Poland several times. He cooperated with leading Polish directors Andrzej Wajda nad Jerzy Skolimowski. In the 70’s he established contact with the budding opposition, Adam Michnik among others. He became the unofficial liaison officer between the countrys’ opposition (the Workers’ Defence Committee) and Kultura in Paris. The Security Service intended to enlist him. In 1976 the candidate for a secret collaborator was listed in the index of persona non grata in the People’s Republic of Poland.